Adaptation of Drosophila melanogaster to high and low osmolarity promotes evolutionary change in the phenotypic plasticity of the larval anal organs - Sivunova, Dana; Yakovleva, Ekaterina; Naimark, Elena; Lysenkov, Sergey; Perfilieva, Ksenia; Markov, Alexander (Biological Communications, 2024)
The anal organs (AO) of Drosophila larvae provide a textbook example of phenotypic developmental plasticity as they expand in low osmolarity conditions and shrink when larvae are reared on a high-salt medium. Waddington (1953) experimentally showed that these plastic changes might undergo “genetic as similation”: the adaptive plastic change in the size of AO under high salinity conditions became hereditary after a few generations of rearing on a high-salt medium. Later attempts to replicate this finding produced ambiguous results. To clarify the question, we analyzed plastic osmolarity-related changes in the size of AO in three D. melanogaster lines adapted to low, intermediate, and high osmolarity during a long-term evolutionary experiment. We failed to replicate the genetic assimilation. However, we find that the reaction norm became wider in the low osmolarity adapted line. Additionally, we studied the fine structure of AO in fly lines using dying, SEM, and microtomography and revealed phenotypic plasticity of nanoscale pits on the surface of AO as well as confirmed the reduction of the epithelial cells of AO in flies adapted to higher osmolarity.